An Evaluation of Neoadjuvant Chemoradiotherapy for Patients with Resectable Pancreatic Ductal Adenocarcinoma. (20th June 2013) - Jiang, Hui; Du, Chi; Cai, Mingwei; He, Hai; Chen, Cheng; Qiu, Jianguo; Wu, Hong
Abstract : Aims. The aim of this study is to compare our results of preoperative chemotherapy followed by pancreaticoduodenectomy (PD) with those of surgery alone in patients with localized resectable pancreatic ductal adenocarcinoma (PDAC). Methods. Outcome data for 112 patients of resectable PDAC who received preoperative chemoradiotherapy followed by PD (group I) between January 2004 and April 2010 were retrospectively analyzed and were compared with selected 120 patients who underwent PD alone (group II) in the same period. Results. Patients in group I had an incidence of locoregional recurrence of 17.1% compared to 30.8% in group II (P = 0 . 03 ). There were no statistically significant differences in postoperative morbidity (27.7% versus 30.8%) and mortality (2.67% versus 3.33%). The 1-, 2-, and 3-year survival rates were estimated at 82.1%, 54%, and 28%, respectively, with NCRT and 65.8%, 29.1%, and 10% without (P = 0.006 ). Nevertheless, preoperative chemotherapy did not reduce the 1-, 3-, and 5-year disease-free survival rates, which were estimated at 58%, 36.6%, and 12.5% with NCRT and 51.7%, 18.3%, and 7.5% without (P = 0.058 ). Conclusions. The treatment of NCRT followed by PD in patients with PDAC has a significantly lower rate of locoregional recurrence and a longer overall survival than those with surgery alone.